Battery foil, secondary battery and electric equipment

By using a composite coating structure in the battery foil, combined with thermal fillers and phase change microcapsules, the problem of phase change materials prone to leakage and increase battery internal resistance in the prior art is solved, and more effective battery thermal management and longer service life are achieved.

CN119812349APending Publication Date: 2025-04-11SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411975418.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing battery thermal management technologies have problems such as phase change materials being prone to leakage, increasing battery internal resistance, and reducing electrochemical performance.

Method used

The battery foil with a composite coating structure includes thermal filler and phase-changing microcapsules. The phase-changing microcapsules are attached to the surface of the thermal filler to form a core-shell structure and improve thermal management performance.

Benefits of technology

It effectively reduces the leakage risk of phase change microcapsules, improves the flexibility and response rate of thermal management, and improves the thermal management performance and service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812349A_ABST
    Figure CN119812349A_ABST
Patent Text Reader

Abstract

The invention provides a battery foil, a secondary battery and electric equipment, and belongs to the technical field of batteries. The battery foil comprises a first metal foil, a second metal foil and a composite coating arranged between the first metal foil and the second metal foil, the composite coating comprises organic silica gel, heat conduction filler and phase change microcapsules, and the phase change microcapsules are attached to the surface of the heat conduction filler. According to the battery foil, the leakage risk of the phase change microcapsules is reduced, the heat conduction path is shorter, the distribution is more uniform, the heat absorption or heat release response rate of the phase change material is improved, the temperature uniformity of the internal roll core is improved, and meanwhile, the original charge-discharge reaction process in the battery is not influenced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery technology, and specifically relates to a battery foil material and a preparation method thereof, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are widely used in aerospace, electronic communications, household appliances, electric vehicles and other fields. However, in the process of further expanding their application scope, in addition to being limited by energy density and power density, the thermal safety issues caused by high-power operation in actual application, as well as capacity decay and lithium precipitation caused by low temperature environment will affect their electrochemical performance and life. It is very necessary to control the maximum temperature and temperature difference of the battery within a reasonable temperature range to ensure that the battery has reliable electrochemical performance, safety and a long service life. Existing battery thermal management strategies include air cooling, liquid cooling, heat pipe cooling, phase change material cooling and hybrid thermal management. The above-mentioned thermal management methods all impose additional cooling measures on the outside of the battery, which not only consumes the battery's additional energy storage supply, but also cannot quickly respond to and absorb the heat generated inside the battery (generally a temperature sensor is required to measure the temperature before starting heating or cooling).

[0003] The prior art discloses that phase change microcapsules are mixed in the electrode material. The phase change microcapsules have a higher phase change heat storage enthalpy value, which can make the electrode absorb excess heat and eliminate the heat peak under overheating conditions; and when the external ambient temperature is low, the phase change microcapsule layer can release the stored heat and heat the battery to avoid the adverse effects of low temperature on the battery operating conditions, overcoming the problem that the heat generated inside the battery cannot be quickly responded to and absorbed. However, since a layer of electrode material mixed with phase change microcapsules is coated on the surface of the foil, the phase change microcapsules are in direct contact with the electrode material, and there is a leakage problem during use. The leaked phase change material will block the ion transmission channel inside the electrode after further solidification, reducing the electrochemical performance of the battery. Secondly, conventional phase change microcapsules do not have electrochemical energy storage capacity. Mixing them in electrode materials will not only increase the internal resistance of the battery, but also reduce the battery capacitance. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present application is to overcome the defects of the prior art that the phase change material is easy to leak, the phase change material increases the internal resistance of the battery, and reduces the electrochemical performance of the battery, thereby providing a battery foil, a secondary battery and an electrical device.

[0005] To this end, this application provides the following technical solutions.

[0006] In a first aspect, the present application provides a battery foil, comprising a first metal foil, a second metal foil, and a composite coating arranged between the first metal foil and the second metal foil; the composite coating comprises organic silica gel, a thermal conductive filler, and phase change microcapsules, and the phase change microcapsules are attached to the surface of the thermal conductive filler.

[0007] In some embodiments, the phase-change microcapsules have a core-shell structure, wherein the core comprises normal alkanes C n H 2n+1 Any two phase change materials in n = 14 to 24. The core of the phase change microcapsule includes two phase change materials, which is beneficial to broaden the temperature range of thermal management.

[0008] In some embodiments, the core includes any two of n-tetradecane, n-hexadecane, n-octadecane, n-eicosane, and n-octacosane.

[0009] In some embodiments, the shell includes an organic shell material, and the organic shell material includes one or more of melamine resin and urea-formaldehyde resin.

[0010] In some embodiments, the shell comprises an inorganic shell material, and the inorganic shell material comprises one or more of silicon dioxide and calcium carbonate.

[0011] In some embodiments, the mass ratio of the thermal conductive filler to the phase change microcapsule is 1:(3-5); the sum of the mass of the thermal conductive filler and the phase change microcapsule is 15-25wt% of the mass of the organic silica gel. The contents of the thermal conductive filler, the phase change microcapsule and the organic silica gel within the above range are conducive to improving the thermal management performance and rate of the composite coating.

[0012] In some embodiments, the particle size of the phase change microcapsule is 2-13 μm. The particle size of the phase change microcapsule is within the above range while ensuring the heat absorption capacity and thermal response rate of the phase change microcapsule.

[0013] In some embodiments, the mass ratio of the two phase change materials in the phase change microcapsules is 0.5 to 1.5, which is beneficial to broaden the temperature range of thermal management and enhance the flexibility of battery thermal management.

[0014] In some embodiments, the thermally conductive filler includes expanded graphite and / or carbon nanotubes. Using expanded graphite and / or carbon nanotubes as thermally conductive fillers can easily form a connected thermally conductive frame, which is beneficial to improving the heat absorption or heat release response rate of the phase change material.

[0015] In some embodiments, the first metal foil and the second metal foil are aluminum foils, the composite coating has a thickness of 1 to 4 μm, and the first metal foil and the second metal foil are each 8 to 14 μm.

[0016] In some embodiments, the first metal foil and the second metal foil are copper foils, the composite coating has a thickness of 1-4 μm, and the first metal foil and the second metal foil are each 4.5-12 μm.

[0017] In some embodiments, the organic silicone is an AB two-component silicone comprising a prepolymer component A and a curing agent component B. In some embodiments, the mass ratio of the prepolymer component A to the curing agent component B is 0.95 to 1.1. The mass ratio of the prepolymer component A to the curing agent component B is within the above range, which can ensure that the composite coating has appropriate flexibility and viscosity.

[0018] In a second aspect, the present application provides a secondary battery, wherein the secondary battery comprises the battery foil material described in the first aspect of the present application.

[0019] In a third aspect, the present application provides an electrical device including the secondary battery.

[0020] The technical solution of this application has the following advantages:

[0021] The composite coating containing phase change microcapsules in the present application is located between two layers of foil and is not in direct contact with the electrode material on the surface of the battery foil, thereby reducing the risk of leakage of the phase change microcapsules. The phase change material is coated inside the shell material, thereby avoiding leakage problems that may be caused by the phase change material after heating and melting. Organic silica gel serves as a soft and sticky base for the composite coating material, allowing it to adhere to the surface of the pretreated metal foil and be evenly distributed inside the battery. Compared with the external phase change material thermal management method, the heat conduction path is shorter and more evenly distributed, which is beneficial to improving the heat absorption or heat release response rate of the phase change material and improving the temperature uniformity of the internal winding core, while not affecting the original charge and discharge reaction process inside the battery. The phase change microcapsules in the present application are attached to the surface of the thermally conductive filler, and the phase change microcapsules are dispersed on the surface of the thermally conductive filler. The thermally conductive framework provided by the thermally conductive filler is beneficial to improving the thermal response efficiency of the phase change microcapsules. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0023] Figure 1 is a schematic diagram of the preparation process of the battery foil material of Example 1;

[0024] Figure 2 Schematic diagram of the phase change microcapsule structure in Example 1.

[0025] Reference numerals:

[0026] 1- core; 2- shell. DETAILED DESCRIPTION

[0027] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0028] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0029] The dual-core phase-change microcapsules in Examples 1 to 3 are dual-core organic shell phase-change microcapsules synthesized by in-situ polymerization, with n-octadecane and n-octacosane as dual-core core materials and melamine resin as shell materials. The schematic structure is shown in FIG. Figure 2 As shown, it includes a core 1 and a shell 2. Preparation process reference Meng X, Qin S, Fan H, et al. Long alkyl chain-grafted carbon nanotube-decorated binary-core phase-change microcapsules for heat energy storage: Synthesis and thermal properties [J]. Solar Energy Materials and Solar Cells, 2020, 212: 110589. The core material of the above-mentioned BMPCMs is 1:1 mass ratio of n-octadecane and n-octacosane, and the shell material is melamine resin, the particle size of which is mainly distributed at about 12 μm, the melting phase change temperature control range is about 26 ° C ~ 55 ° C, and the phase change enthalpy value is 199.8 J / g.

[0030] Example 1

[0031] This embodiment provides a battery foil material, which is a composite aluminum foil, which includes aluminum foil, composite coating, and aluminum foil in sequence. The composite coating thickness of the middle interlayer is 3 μm, and the thickness of the upper and lower aluminum foils is 10 μm respectively.

[0032] The preparation method of the battery foil of this embodiment is as follows: Figure 1 As shown, the following steps are included:

[0033] Step 1: Preparation of composite coating material:

[0034] First, binuclear phase change microcapsules (BMPCMs) and expanded graphite (EG, Shenzhen Ruijit Biotechnology Co., Ltd.) were weighed and placed in a container at a weight ratio of 4:1. At room temperature, the closed container containing EG and BMPCMs was placed on an oscillating shaker and oscillated and mixed at a speed of 250 rpm for 3 hours to allow BMPCMs to evenly adhere to the surface of the EG material. Finally, the EG-BMPCMs blend was dried in a forced air oven at 27°C for 1 hour.

[0035] AB two-component silicone (Shenzhen Wangzhong Synthetic Material Factory, model wz-9800) includes prepolymer component A liquid and curing agent component B liquid. The prepolymer component A liquid and curing agent component B liquid with a weight ratio of 11:10 are placed in a smooth container and mixed and stirred at room temperature for 10 minutes. Then, EG-BMPCMs blend is added, and the mass of EG-BMPCMs blend is 20wt% of the mass of AB two-component silicone. Stirring is continued at room temperature for 1.5 hours to ensure that the EG-BMPCMs blend is evenly distributed in the AB two-component organic silicone to obtain a composite coating material.

[0036] The above-mentioned EG microscopic surface structure is porous, which effectively increases the attachment area of ​​BMPCMs and the thermal conductive grid path of the composite coating.

[0037] Step 2: firstly coat a layer of the composite coating material obtained in step 1 on the surface of the aluminum foil, and then attach another aluminum foil to the coating surface to finally form a sandwich-shaped composite foil material.

[0038] Step 3: In a vacuum environment of 50-100 KPa, roll the composite foil at a pressure of 3.5 MPa to make the intermediate coating uniform and smooth while removing bubbles.

[0039] Step 4: Place the composite foil obtained in step 3 in a vacuum oven at 50° C. and dry for 6 hours to obtain a battery foil.

[0040] Example 2

[0041] This embodiment provides a battery foil material, which is a composite copper foil, which includes copper foil, composite coating and copper foil in sequence. The thickness of the composite coating of the middle interlayer is 3 μm, and the thickness of the upper and lower copper foils is 4.5 μm respectively.

[0042] The preparation method of the battery foil of this embodiment comprises the following steps:

[0043] Step 1: Preparation of composite coating material:

[0044] First, binuclear phase change microcapsules (BMPCMs) and expanded graphite (EG, Shenzhen Ruijit Biotechnology Co., Ltd.) were weighed and placed in a container at a weight ratio of 5:1. At room temperature, the closed container containing EG and BMPCMs was placed on an oscillating shaker and oscillated and mixed at a speed of 250 rpm for 3 hours to allow BMPCMs to evenly adhere to the surface of the EG material. Finally, the EG-BMPCMs blend was dried in a forced air oven at 27°C for 1 hour.

[0045] AB two-component silicone (Shenzhen Wangzhong Synthetic Material Factory, model wz-9800) includes prepolymer component A liquid and curing agent component B liquid. The prepolymer component A liquid and curing agent component B liquid with a weight ratio of 11:10 are placed in a smooth container and mixed and stirred at room temperature for 10 minutes. Then, EG-BMPCMs blend is added, and the mass of EG-BMPCMs blend is 20wt% of the mass of AB two-component silicone. Stirring is continued at room temperature for 1.5 hours to ensure that the EG-BMPCMs blend is evenly distributed in the AB two-component organic silicone to obtain a composite coating material.

[0046] The above-mentioned EG microscopic surface structure is porous, which effectively increases the attachment area of ​​BMPCMs and the thermal conductive grid path of the composite coating.

[0047] Step 2: firstly coat a layer of the composite coating material obtained in step 1 on the surface of the copper foil, and then attach another copper foil to the coating surface to finally form a sandwich-shaped composite foil material.

[0048] Step 3: In a vacuum environment of 50-100 KPa, roll the composite foil at a pressure of 3.5 MPa to make the intermediate coating uniform and smooth while removing bubbles.

[0049] Step 4: Place the composite foil obtained in step 3 in a vacuum oven at 50° C. and dry for 6 hours to obtain a battery foil.

[0050] Example 3

[0051] This embodiment provides a battery foil material, which is a composite copper foil, which includes copper foil, composite coating and copper foil in sequence. The composite coating thickness of the middle interlayer is 3 μm, and the thickness of the upper and lower copper foils is 4.5 μm respectively.

[0052] The preparation method of the battery foil of this embodiment comprises the following steps:

[0053] Step 1: Preparation of composite coating material:

[0054] First, binuclear phase change microcapsules (BMPCMs) and carbon nanotubes (CNT, Shanghai Aladdin Biochemical Technology Co., Ltd.) were weighed and placed in a container at a weight ratio of 3:1. At room temperature, the closed container containing CNT and BMPCMs was placed on an oscillating shaker and oscillated and mixed at a speed of 250 rpm for 3 hours to uniformly disperse the BMPCMs on the surface of the CNT material. Finally, the CNT-BMPCMs blend was dried in a forced air oven at 27°C for 1 hour.

[0055] AB two-component silicone (Shenzhen Wangzhong Synthetic Materials Factory, model wz-9800) includes prepolymer component A liquid and curing agent component B liquid. The prepolymer component A liquid and curing agent component B liquid in a weight ratio of 1:1 are placed in a smooth container and mixed and stirred at room temperature for 10 minutes. Subsequently, CNT-BMPCMs blend is added, and the mass of CNT-BMPCMs blend is 20wt% of the mass of AB two-component silicone. Stirring is continued at room temperature for 1.5 hours to ensure that the CNT-BMPCMs blend is evenly distributed in the AB two-component organic silicone to obtain a composite coating material.

[0056] Step 2: firstly coat a layer of the composite coating material prepared in step 1 on the surface of the pretreated copper foil, and then attach the upper pretreated copper foil to the coating surface, so as to finally form a sandwich-shaped composite foil material.

[0057] Step 3: In a vacuum environment of 50-100 KPa, roll the composite foil at a pressure of 3.5 MPa to make the intermediate coating uniform and smooth while removing bubbles.

[0058] Step 4: Place the composite foil obtained in step 3 in a vacuum oven at 50° C. and dry for 6 hours to obtain a battery foil.

[0059] Example 4

[0060] This embodiment provides a battery foil material, which is a composite aluminum foil, which includes aluminum foil, composite coating, and aluminum foil in sequence. The composite coating thickness of the middle interlayer is 3 μm, and the thickness of the upper and lower aluminum foils is 10 μm respectively.

[0061] The preparation method of the battery foil of this embodiment comprises the following steps:

[0062] Step 1: Preparation of composite coating material:

[0063] First, binuclear phase change microcapsules (BMPCMs) and expanded graphite (EG, Shenzhen Ruijit Biotechnology Co., Ltd.) were weighed and placed in a container at a weight ratio of 4:1. At room temperature, the closed container containing EG and BMPCMs was placed on an oscillating shaker and oscillated and mixed at a speed of 250 rpm for 3 hours to uniformly disperse BMPCMs in the EG three-dimensional porous structure. Finally, the EG-BMPCMs blend was dried in a forced air oven at 27°C for 1 hour.

[0064] AB two-component silicone (Shenzhen Wangzhong Synthetic Material Factory, model wz-9800) includes prepolymer component A liquid and curing agent component B liquid. The prepolymer component A liquid and curing agent component B liquid with a weight ratio of 11:10 are placed in a smooth container and mixed and stirred at room temperature for 10 minutes. Then, EG-BMPCMs blend is added, and the mass of EG-BMPCMs blend is 20wt% of the mass of AB two-component silicone. Stirring is continued at room temperature for 1.5 hours to ensure that the EG-BMPCMs blend is evenly distributed in the AB two-component organic silicone to obtain a composite coating material.

[0065] The core material of the BMPCMs described in this embodiment is n-octadecane and n-octacosane in a mass ratio of 1:1, and the shell material is silicon dioxide, the particle size of which is mainly distributed at around 3 μm, the melting phase change temperature control range is around 25°C to 55°C, and the phase change enthalpy value is 192.6 J / g.

[0066] The above-mentioned BMPCMs material is a dual-core inorganic shell phase change microcapsule with n-octadecane and n-octacosane as the dual-core core material and silicon dioxide as the shell material, which is synthesized by interfacial catalytic hydrolysis and polycondensation. Preparation process reference: Preparation and performance study of alkylated carbon nanotube modified binary core material phase change microcapsules [D]. DOI: 10.27321 / d.cnki.gszdu.2020.000735.

[0067] The above-mentioned EG microscopic surface structure is porous, which effectively increases the attachment area of ​​BMPCMs and the thermal conductive grid path of the composite coating.

[0068] Step 2: firstly coat a layer of the composite coating material obtained in step 1 on the surface of the aluminum foil, and then attach another aluminum foil to the coating surface to finally form a sandwich-shaped composite foil material.

[0069] Step 3: In a vacuum environment of 50-100 KPa, roll the composite foil at a pressure of 3.5 MPa to make the intermediate coating uniform and smooth while removing bubbles.

[0070] Step 4: Place the composite foil obtained in step 3 in a vacuum oven at 50° C. and dry for 6 hours to obtain a battery foil.

[0071] Example 5

[0072] The preparation method of the battery foil in this embodiment is basically the same as that in Embodiment 1, except that the core material (core) of the phase change microcapsule in this embodiment is a phase change material n-octadecane.

[0073] Example 6

[0074] The preparation method of the battery foil of this embodiment is basically the same as that of Embodiment 1, except that the mass ratio of the thermal conductive filler to the phase change microcapsule in this embodiment is 1:8.

[0075] Example 7

[0076] This embodiment provides a battery foil material, which is a composite aluminum foil, which includes aluminum foil, composite coating, and aluminum foil in sequence. The thickness of the composite coating of the middle interlayer is 4 μm, the thickness of the upper aluminum foil is 8 μm, and the thickness of the lower aluminum foil is 14 μm.

[0077] The preparation method of the battery foil of this embodiment is as follows: Figure 1 As shown, the following steps are included:

[0078] Step 1: Preparation of composite coating material:

[0079] First, binuclear phase change microcapsules (BMPCMs) and expanded graphite (EG, Shenzhen Ruijit Biotechnology Co., Ltd.) were weighed and placed in a container at a weight ratio of 3:1. At room temperature, the closed container containing EG and BMPCMs was placed on an oscillating shaker and oscillated and mixed at a speed of 250 rpm for 3 hours to allow BMPCMs to evenly adhere to the surface of the EG material. Finally, the EG-BMPCMs blend was dried in a forced air oven at 27°C for 1 hour.

[0080] Dual-core phase change microcapsules (BMPCMs) are a type of dual-core organic shell phase change microcapsules synthesized by in-situ polymerization with n-octadecane and n-octacosane as dual-core core materials and melamine resin as shell material (MF shell). Figure 2As shown. Preparation process reference Meng X, Qin S, Fan H, et al. Long alkyl chain-grafted carbon nanotube-decorated binary-core phase-change microcapsules for heat energy storage: Synthesis and thermal properties [J]. Solar Energy Materials and Solar Cells, 2020, 212: 110589. The core material of the above-mentioned BMPCMs is 0.5:1 mass ratio of n-octadecane and n-octacosane, and the shell material is melamine resin, and its particle size is mainly distributed around 3μm.

[0081] AB two-component silicone (Shenzhen Wangzhong Synthetic Material Factory, model wz-9800) includes prepolymer component A liquid and curing agent component B liquid. The prepolymer component A liquid and curing agent component B liquid with a weight ratio of 0.95:1 are placed in a smooth container and mixed and stirred at room temperature for 10 minutes. Then, EG-BMPCMs blend is added, and the mass of EG-BMPCMs blend is 15wt% of the mass of AB two-component silicone. Stirring is continued at room temperature for 1.5 hours to ensure that the EG-BMPCMs blend is evenly distributed in the AB two-component organic silicone to obtain a composite coating material.

[0082] The above-mentioned EG microscopic surface structure is porous, which effectively increases the attachment area of ​​BMPCMs and the thermal conductive grid path of the composite coating.

[0083] Step 2: firstly coat a layer of the composite coating material obtained in step 1 on the surface of the aluminum foil, and then attach another aluminum foil to the coating surface to finally form a sandwich-shaped composite foil material.

[0084] Step 3: In a vacuum environment of 50-100Kpa, roll the composite foil at a pressure of 3Mpa to make the intermediate coating uniform and smooth while removing bubbles.

[0085] Step 4: Place the composite foil obtained in step 3 in a vacuum oven at 30° C. and dry for 10 hours to obtain a battery foil.

[0086] Example 8

[0087] This embodiment provides a battery foil material, which is a composite copper foil, which includes copper foil, composite coating, and copper foil in sequence. The composite coating thickness of the middle interlayer is 1 μm, the upper copper foil is 10 μm, and the lower copper foil is 12 μm.

[0088] The preparation method of the battery foil of this embodiment comprises the following steps:

[0089] Step 1: Preparation of composite coating material:

[0090] First, binuclear phase change microcapsules (BMPCMs) and expanded graphite (EG, Shenzhen Ruijit Biotechnology Co., Ltd.) were weighed and placed in a container at a weight ratio of 5:1. At room temperature, the closed container containing EG and BMPCMs was placed on an oscillating shaker and oscillated and mixed at a speed of 250 rpm for 3 hours to allow BMPCMs to evenly adhere to the surface of the EG material. Finally, the EG-BMPCMs blend was dried in a forced air oven at 27°C for 1 hour.

[0091] Dual-core phase change microcapsules (BMPCMs) are a type of dual-core organic shell phase change microcapsules synthesized by in-situ polymerization with n-octadecane and n-octacosane as dual-core core materials and melamine resin as shell material (MF shell). Figure 2 As shown. Preparation process reference Meng X, Qin S, Fan H, et al. Long alkyl chain-grafted carbon nanotube-decorated binary-core phase-change microcapsules for heat energy storage: Synthesis and thermal properties [J]. Solar Energy Materials and Solar Cells, 2020, 212: 110589. The core material of the above-mentioned BMPCMs is n-octadecane and n-octacosane in a mass ratio of 1.5:1, and the shell material is melamine resin, and its particle size is mainly distributed around 6 μm.

[0092] AB two-component silicone (Shenzhen Wangzhong Synthetic Material Factory, model wz-9800) includes prepolymer component A liquid and curing agent component B liquid. The prepolymer component A liquid and curing agent component B liquid in a weight ratio of 1:1 are placed in a smooth container and mixed and stirred at room temperature for 10 minutes. Then, EG-BMPCMs blend is added, and the mass of EG-BMPCMs blend is 25wt% of the mass of AB two-component silicone. Stirring is continued at room temperature for 1.5 hours to ensure that the EG-BMPCMs blend is evenly distributed in the AB two-component organic silicone to obtain a composite coating material.

[0093] The above-mentioned EG microscopic surface structure is porous, which effectively increases the attachment area of ​​BMPCMs and the thermal conductive grid path of the composite coating.

[0094] Step 2: firstly coat a layer of the composite coating material obtained in step 1 on the surface of the copper foil, and then attach another copper foil to the coating surface to finally form a sandwich-shaped composite foil material.

[0095] Step 3: In a vacuum environment of 50-100 KPa, roll the composite foil at a pressure of 5 MPa to make the intermediate coating uniform and smooth while removing bubbles.

[0096] Step 4: Place the composite foil obtained in step 3 in a vacuum oven at 55° C. and dry for 3 hours to obtain a battery foil.

[0097] Comparative Example 1

[0098] The battery foil material of this comparative example is a single AB two-component organic silica gel without thermal conductive filler and phase change microcapsule coated between the upper and lower aluminum foils with a thickness of 10 μm, and the thickness of the organic silica gel layer is 2 mm.

[0099] Comparative Example 2

[0100] The battery foil material of this comparative example is a single AB two-component organic silica gel without thermal conductive filler and phase change microcapsule coated between the upper and lower copper foils with a thickness of 4.5 μm, and the thickness of the organic silica gel layer is 2 mm.

[0101] Test example

[0102] The composite coating materials prepared in Example 1 and Example 4 were coated in the middle of the upper and lower aluminum foils with a thickness of 10 μm, and the coating thickness was 2 mm, as test samples of Example 1 and Example 4. The composite coating materials prepared in Example 2 and Example 3 were coated in the middle of the upper and lower copper foils with a thickness of 4.5 μm, and the coating thickness was 2 mm, as test samples of Example 2 and Example 3. 5*5 cm composite foil test samples of Example 1 to Example 4 and Comparative Example 1 to Comparative Example 2 were cut respectively, and placed in a refrigerator together with a PVDF (polyvinylidene fluoride) gasket of the same size and thickness of 1 cm to cool to about 0°C, and then the test samples of Example 1 to 4 and Comparative Example 1 to Comparative Example 2 were placed on the PVDF gasket and then placed on a 60°C heating table for heating.

[0103] Table 1 Temperature difference between the embodiment and the comparative example during heating (°C)

[0104]

[0105] Comparative Example 1 does not contain thermally conductive fillers and phase change microcapsules. The surface temperature of the composite foil increases monotonically during the entire heating process without fluctuations. When the surface temperature of Comparative Example 1 reaches 45°C, the surface temperature of the composite aluminum foil of Example 1 is 2°C lower than that of the composite foil. When the surface temperature of Comparative Example 1 reaches 60°C, the surface temperature of the composite aluminum foil of Example 1 is 3.5°C lower than that of the composite foil. This is attributed to the fact that the thermally conductive fillers inside the composite coating make Example 1 have better thermal conductivity than Comparative Example 1, and transfer heat to the binuclear phase change microcapsules faster. When the temperature of the binuclear phase change microcapsules exceeds 26°C and 45°C, the phase change temperatures of n-octadecane and n-octacosane are reached respectively, and the binuclear phase change microcapsules undergo melting and heat absorption, which reduces the temperature rise of the composite aluminum foil.

[0106] The shell material of the phase change microcapsule in Example 4 is silicon dioxide, and the particle size is mainly distributed around 3 μm. At the same time, since the thermal conductivity of the phase change microcapsule with inorganic wall material of silicon dioxide is greater than that of the phase change microcapsule with organic wall material of melamine resin, but the phase change melting enthalpy value is slightly lower than the latter. Compared with Comparative Example 1, when the surface temperature of Comparative Example 1 reaches 45 and 60°C respectively, the surface temperature of Example 4 is reduced by 2.5°C and 2.9°C respectively.

[0107] The core material of the phase change microcapsule in Example 5 is all n-octadecane. During the whole heating process, when the temperature reaches 26°C, the single-component core material octadecane inside the phase change microcapsule will melt and absorb heat. Compared with the surface temperature of Comparative Example 1 reaching 45°C, the surface temperature of Example 5 is about 3.6°C lower than that of Comparative Example 1. When the composite foil of this example continues to be heated, since the core material octadecane has basically melted and no longer absorbs heat, compared with the surface temperature of Comparative Example 1 reaching 60°C, the surface temperature of the composite foil of Example 5 is only 0.8°C lower than that of Comparative Example 1, and the thermal management temperature range is relatively narrow.

[0108] The preparation method of the composite foil of Example 6 is basically the same as that of Example 1, except that the mass ratio of the thermal conductive filler to the phase change microcapsule in this example is 1:8, the thermal conductivity of the composite foil is poorer than that of Example 1, and the thermal response of the internal phase change material during the heating process is slow. Therefore, although the content of the phase change microcapsule increases, the heat absorption rate of the core material phase change inside the phase change microcapsule in the coating decreases. When the surface temperature of Comparative Example 1 reaches 45°C and 60°C, respectively, Example 6 only decreases by 1.2°C and 2.6°C, respectively. Therefore, it is necessary to select a moderate ratio of phase change microcapsules and thermal conductive fillers to comprehensively improve the thermal management performance and rate of the composite coating.

[0109] Comparative Example 2 does not contain thermal conductive fillers and phase change microcapsules, and the surface temperature of the composite foil increases monotonically during the entire heating process without fluctuations. In Example 2, the ratio of expanded graphite to phase change microcapsules is increased to 1:5. When the surface temperature of Comparative Example 2 reaches 45°C, the surface temperature of the composite copper foil of Example 2 is 2.8°C lower than that of the composite copper foil. When the surface temperature of Comparative Example 2 reaches 60°C, the surface temperature of the composite copper foil of Example 2 is 4°C lower than that of the composite copper foil.

[0110] In Example 3, the ratio of thermal conductive filler to phase change microcapsule is 1:3, and the thermal conductive filler is carbon nanotube, which is easier to form a connected thermal conductive frame than conventional sheet or granular thermal conductive fillers. Compared with Comparative Example 2, when the surface temperature of Comparative Example 2 reaches 45 and 60°C, the surface temperature of Example 3 is reduced by 1.8 and 2.8°C, respectively.

[0111] This application reduces the risk of leakage of phase change microcapsules. Compared with the external phase change material thermal management method, the heat conduction path is shorter and more evenly distributed, which is conducive to improving the heat absorption or heat release response rate of the phase change material and improving the internal winding core temperature uniformity, while not affecting the original charging and discharging reaction process inside the battery.

[0112] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection created by this application.

Claims

1. A battery foil, characterized in that: It comprises a first metal foil, a second metal foil and a composite coating arranged between the first metal foil and the second metal foil; the composite coating comprises organic silica gel, thermal conductive filler and phase change microcapsules, and the phase change microcapsules are attached to the surface of the thermal conductive filler.

2. The battery foil according to claim 1, characterized in that: The phase-change microcapsule has a core-shell structure, wherein the core comprises normal alkane C n H 2n+1 Any two phase change materials in, n=14~24.

3. The battery foil according to claim 2, characterized in that: The core includes any two of n-tetradecane, n-hexadecane, n-octadecane, n-eicosane, and n-octacosane.

4. The battery foil material according to any one of claims 2 to 3, characterized in that: The shell includes an organic shell material, and the organic shell material includes one or more of melamine resin and urea-formaldehyde resin; And / or, the shell comprises an inorganic shell material, and the inorganic shell material comprises one or more of silicon dioxide and calcium carbonate.

5. The battery foil according to any one of claims 2 to 3, characterized in that: The mass ratio of the two phase change materials in the phase change microcapsule is 0.5-1.

5.

6. The battery foil according to claim 1, characterized in that: The mass ratio of the thermal conductive filler to the phase change microcapsule is 1:(3-5), and the sum of the mass of the thermal conductive filler and the phase change microcapsule is 15-25wt% of the mass of the organic silica gel.

7. The battery foil according to claim 1, characterized in that: The thermally conductive filler includes expanded graphite and / or carbon nanotubes.

8. The battery foil according to claim 1, characterized in that: The organic silica gel is an AB two-component silica gel including a prepolymer component A and a curing agent component B, and the mass ratio of the prepolymer component A to the curing agent component B is 0.95-1.

1.

9. A secondary battery, characterized in that: The invention comprises the battery foil material according to any one of claims 1 to 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Patent Citations

  • Graphene-based heat conduction silica gel phase change composite material and preparation method thereof

    CN105348797A

  • Heat-absorbing pouring sealant and a battery thereof

    CN109722215A

  • Composite binary phase-change material and application thereof in battery thermal management system

    CN111082185A

  • Phase change temperature control type electrode, preparation method thereof and lithium ion battery

    CN111430709A

  • Composite phase change material for lithium battery and preparation method of composite phase change material

    CN115305062A

Cited By

  • Oxide / gel composite solid electrolyte and preparation method and application thereof

    CN120581687A